Charting transnational fields methodology for a political sociology of knowledge - Schmidt-Wellenburg, Christian; Bernhard, Stefan 1977- (Routledge, Taylor & Francis Group, 2020)
"The volume provides a field-analytical methodology for researching knowledge based sociopolitical processes of transnationalization. Drawing on the seminal work by Pierre Bourdieu, we apply concepts of practice, habitus, and field to phenomena such as cross-national social trajectories, international procedures of evaluation, standardization and certification or supranational political structures. These transnational phenomena form part of general political struggles that legitimate social relationships in and beyond the nation state. Part 1 on "Methodological Foundations" discusses the consequences of Bourdieu's epistemology and methodology for theorizing and investigating transnational phenomena. The contributions show the import of field-theoretical concepts for post-national insights. Part 2 on "Investigating Political Fields" presents exemplary case studies in diverse research areas such as colonial imperialism, international academic rankings, European policy fields, and local school policy. While focusing on their research objects, the contributions also give an insight into the mechanisms involved in processes of transnationalization. The volume is an invitation for sociologists, political scientists and scholars in adjacent research areas to engage with reflexive and relational research practice and to further develop field-theoretical thought"--
Keywords: Internationale Politik; Methodologie; Wissenschaftssoziologie; Feldtheorie -- Soziologie; Forschung; Sozialpsychologie; Wissenssoziologie; Politische Soziologie; Transnationale Politik; Transnationalism / Research / Methodology; Transnationalism / Study and teaching; Field theory (Social psychology); Political sociology; Knowledge, Sociology of; Aufsatzsammlung